2019
DOI: 10.1007/s10948-019-05302-6
|View full text |Cite
|
Sign up to set email alerts
|

The Unconventional Copper Oxide Superconductor with Conventional Constitution

Abstract: A new Ba 2 CuO 4-y superconductor with critical temperature (T c) exceeding 70 K was discovered. The X-ray absorption measurement gives evidence that this cuprate resembles La 2 CuO 4 but is doped with a fairly large amount of holes, while in contrast to the so far known hole-doped high-T c cuprates, the new cuprate possesses a much shorter local apical oxygen distance as well as much expanded in-plane Cu-O bond, leading to unprecedented compressed local octahedron. In compressed local octahedron, the Cu3d3z 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…What distinguishes the CuO 2 /BSCCO system from the well known cuprates is that a highly hole-overdoped regime can be reached due to the charge transfer from the monolayer to the BSCCO substrate, which takes place in order to maintain charge neutrality 8 . It should be noted, that such high hole-doping levels can also be obtained as a result of the the high-pressure ox-idized synthesis of the bulk system Ba 2 CuO 4−y (Ba214) in which superconductivity has been reported very recently 9,10 , as well as in Sr 2 CuO 4−δ , discussed already some time ago 11 .…”
Section: Introductionmentioning
confidence: 94%
“…What distinguishes the CuO 2 /BSCCO system from the well known cuprates is that a highly hole-overdoped regime can be reached due to the charge transfer from the monolayer to the BSCCO substrate, which takes place in order to maintain charge neutrality 8 . It should be noted, that such high hole-doping levels can also be obtained as a result of the the high-pressure ox-idized synthesis of the bulk system Ba 2 CuO 4−y (Ba214) in which superconductivity has been reported very recently 9,10 , as well as in Sr 2 CuO 4−δ , discussed already some time ago 11 .…”
Section: Introductionmentioning
confidence: 94%
“…It is shown by X-ray absorption measurement that in the compressed octahedron, the 3dz 2 -r 2 orbital should be lifted above the 3dx 2 -y 2 orbital resulting in significant 3D nature in addition to the conventional 3dx 2 -y 2 orbital [ 59 ]. Based on these data, it was suggested that Ba 2 CuO 4-y is a member of a different branch of high-T c cuprate materials [ 60 , 61 ]. Another example of cuprate synthesized at high-pressure is Cu 0.75 Mo 0.25 Sr 2 YCu 2 O 7.54 , it has crystal structure similar to YBCO123 phase and exhibited T c at ~ 87 K being strongly overdoped (nominal content p ~ 0.46) [ 62 , 63 ].…”
Section: La 2 Cuo 4 -Relatedmentioning
confidence: 99%
“…Copper(I) oxide (Cu 2 O) and copper(II) oxide (CuO), the most common initial corrosion product formed during the slow oxidation of metallic copper in contact with the atmosphere, play a special role because they are nontoxic, cheap, and have unique optoelectronic properties, owing to which they have a broad range of technological and medical applications. Applications range from the production of electrodes, sensors, efficient photocatalysts driven by visible light, 14 solar energy conversion systems, 15 optoelectronics, lithium-ion batteries, 16 and superconductors 17 to cosmetics and textile components, 18 antiseptics, and bactericides used in daily life or to eliminate pathogens in the aquatic environment. 19 CuO and Cu 2 O are p-type semiconductors (E g = 1.2−1.8 and 2.17 eV, respectively).…”
Section: ■ Introductionmentioning
confidence: 99%